The Independent Gradient Model: A New Approach for Probing Strong and Weak Interactions in Molecules from Wave Function Calculations. Issue 6 (30th January 2018) - Lefebvre, Corentin; Khartabil, Hassan; Boisson, Jean‐Charles; Contreras‐García, Julia; Piquemal, Jean‐Philip; Hénon, Eric
Abstract: Extraction of the chemical interaction signature from local descriptors based on electron density (ED) is still a fruitful field of development in chemical interpretation. In a previous work that used promolecular ED (frozen ED), the new descriptor, δ g, was defined. It represents the difference between a virtual upper limit of the ED gradient ( ∇ ρ I G M, IGM=independent gradient model) that represents a noninteracting system and the true ED gradient ( ∇ ρ ). It can be seen as a measure of electron sharing brought by ED contragradience. A compelling feature of this model is to provide an automatic workflow that extracts the signature of interactions between selected groups of atoms. As with the noncovalent interaction (NCI) approach, it provides chemists with a visual understanding of the interactions present in chemical systems. ∇ ρ I G M is achieved simply by using absolute values upon summing the individual gradient contributions that make up the total ED gradient. Hereby, we extend this model to relaxed ED calculated from a wave function. To this end, we formulated gradient‐based partitioning (GBP) to assess the contribution of each orbital to the total ED gradient. We highlight these new possibilities across two prototypical examples of organic chemistry: the unconventional hexamethylbenzene dication, with a hexa‐coordinated carbon atom, and β‐thioaminoacrolein. It will be shown how a bond‐by‐bond picture can be obtained from a wave function, which opens the way to monitor specific interactions along reaction paths. Abstract : Take a fresh look : The new δ g ‐IGM (IGM=independent gradient model) approach, hereby extended to electron density obtained from quantum mechanics, is able to provide chemists with a visual understanding of interactions by specifically probing a given atom pair in a molecule. It paves the way for targeted mechanistic exploration of reactions.